Impact of Benevolence, Integrity, and Ability on Trust in Supervisor - Akhlaq, Madiha; Kiran, Kokab (iRASD Journal of Management, 2022)
The purpose of this paper is to examine the impact of Benevolence, Integrity, and Ability on trust in supervisors in Karachi, Pakistan. To perform this research, a quantitative study was conducted and a structured questionnaire was designed and distributed among the 300 employees in the manufacturing industry. The findings of this research are to discover the relationship between benevolence, integrity, and the ability to trust a supervisor. This is academic research and is conducted in Karachi, Pakistan. This research is done to find out the trustworthiness attribute that is most important and effective to predict employee trust in the supervisor. Supervisors should have trustworthiness attributes such as benevolence, integrity, and the ability to gain employees’ trust and decrease the anxiety and avoidance of employees at work.